Algorithmic Presentation of the Independent Work of the Students of the Vocational Pedagogical University in the Conditions of the Synchronous Pedagogical Control. Issue 8 (2016) - Dneprov, Sergey A.; Telepova, Tatiana P.; Naumova, Olga A.; Izmaylov, Ayrat M.
No abstract available